2020
DOI: 10.1007/s11042-020-09431-2
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting SVM for medical images using Quadtree

Abstract: In this paper, we propose a quadtree based approach to capture the spatial information of medical images for explaining nonlinear SVM prediction. In medical image classification, interpretability becomes important to understand why the adopted model works. Explaining an SVM prediction is difficult due to implicit mapping done in kernel classification is uninformative about the position of data points in the feature space and the nature of the separating hyperplane in the original space. The proposed method fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Further, we established and validated a stable ML model based on these features to predict edema after EVT in acute stroke patients. The 7 ML models in our study have been proven to have good prediction or classification performance in the medical imaging ( Erickson et al, 2017 ; Kim et al, 2020 ; Shukla et al, 2020 ). We demonstrated that the Bayes model based on DWI + CSF FLAIR and the RF model based on DWI + CSF DWI had the highest AUC value and the most stability, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Further, we established and validated a stable ML model based on these features to predict edema after EVT in acute stroke patients. The 7 ML models in our study have been proven to have good prediction or classification performance in the medical imaging ( Erickson et al, 2017 ; Kim et al, 2020 ; Shukla et al, 2020 ). We demonstrated that the Bayes model based on DWI + CSF FLAIR and the RF model based on DWI + CSF DWI had the highest AUC value and the most stability, respectively.…”
Section: Discussionmentioning
confidence: 85%
“…Deep learning (DL) models, according to recent research, can learn from irrelevant data and make decisions based on that data [ 43 , 44 , 45 , 46 ], even though high-performing networks’ performances cannot be extrapolated to real-world applications. In contrast to ordinary X-rays, the segmented lungs helped the CNN model to identify the primary Region of Interest (ROI).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the Radial Sigma SVM model performed better than other machine learning models. Through linear or nonlinear kernel functions (Radial SVM), SVM is a supervised learning classification algorithm that constructs a hyperplane in a higher dimensional space [ 69 ]. Across all tasks, we found that overall prediction accuracy was high.…”
Section: Discussionmentioning
confidence: 99%